2019
DOI: 10.3349/ymj.2019.60.6.509
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Melanoma Cell-Selective Apoptosis Using Anti-HER2 Antibody-Conjugated Gold Nanoparticles

Abstract: Purpose This study was conducted to verify the induction and mechanism of selective apoptosis in G361 melanoma cells using anti-HER2 antibody-conjugated gold nanoparticles (GNP-HER2). Materials and Methods Following GNP-HER2 treatment of G361 cells, cell cycle arrest and apoptosis were measured by WST-1 assay, Hemacolor staining, Hoechst staining, immunofluorescence staining, fluorescence-activated cell sorting analysis, and Western blotting. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…In contrast, SCC-25 cells treated with PD-L1 ab + GNP showed strong red staining in the cytoplasm around the nucleus (Figure 3). Similar to a previous study [34], higher levels of antibody-GNP uptake were observed in the cancer cells. These results confirmed the selective binding of SCC-25 cells by the PD-L1 antibody + GNP.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, SCC-25 cells treated with PD-L1 ab + GNP showed strong red staining in the cytoplasm around the nucleus (Figure 3). Similar to a previous study [34], higher levels of antibody-GNP uptake were observed in the cancer cells. These results confirmed the selective binding of SCC-25 cells by the PD-L1 antibody + GNP.…”
Section: Discussionsupporting
confidence: 89%
“…It encodes the HER2 receptor, which is a tyrosine-kinase receptor and a tumor factor from a superfamily of EGFR markers that controls growth, survival, adhesion and migration of the cells. It follows an intracellular signal pathway that controls enhancement or suppression of the cell [15]. Mutations in the ERBB2 gene that carry a gene transcription for HER2 receptors, can lead to uncontrolled cell proliferation and oncogenesis.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…For instance, the expression of cluster of differentiation 24 (CD24) is closely intertwined with tumorigenesis and neoplastic diseases. 181 CD24-GNPs have proven to be promising and highly sensitive biomarkers in diagnosing salivary gland tumors and predicting prognosis. 182 Another example is in distinguishing between oral lesions, where GNR-EGFR monoclonal antibodies have been deployed to differentiate between benign and potentially malignant human oral lesions.…”
Section: Engineeringmentioning
confidence: 99%
“…GNSs are reported for use in specific treatments for melanomas. 181,206 Melanoma cells overexpress focal adhesion kinase (FAK) compared with normal cells. Choi et al combined GNPs with antibodies targeting phosphorylated FAK, and found a selective killing effect on melanoma cells with non-thermal atmospheric pressure plasma by inducing apoptosis.…”
Section: Chem Soc Revmentioning
confidence: 99%